The bride and the dowry : Israel, Jordan, and the Palestinians in the aftermath of the June 1967 War - Raz, Avi. (New Haven : Yale University Press, 2012)
Israel's victory in the June 1967 Six Day War provided a unique opportunity for resolving the decades-old Arab-Zionist conflict. Having seized the West Bank, the Gaza Strip, the Sinai Peninsula, and the Golan Heights, Israel for the first time in its history had something concrete to offer its Arab neighbors: it could trade land for peace. Yet the political deadlock persisted after the guns fell silent. This book sets outto find out why. Avi Raz places Israel's conduct under an uncompromising lens. He meticulously examines the critical two years following the June war and substantially revises our understanding of how and why Israeli-Arab secret contacts came to naught. Mining newly declassified records in Israeli, American, British, and UN archives, as well as private papers of individual participants, Raz dispels the myth of overall Arab intransigence and arrives at new and unexpected conclusions. In short, he concludes that Israel's postwar diplomacy was deliberately ineffective because its leaders preferred land over peace with its neighbors. The book throws a great deal of light not only on the post-1967 period but also on the problems and pitfalls of peacemaking in the Middle East today.
EIGHT: The Double Game Redoubled: Mid-Mayâ€?October 1968NINE: â€œThe Whole World Is Against Usâ€?: Epilogue -- Notes -- Sources and Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Israel-Arab War, 1967 -- Influence; Arab-Israeli conflict -- 1967-1973.; Israel-Arab War, 1967.; Conflit israélo-arabe -- 1967-1973.; Guerre israélo-arabe, 1967.; Guerre israélo-arabe, 1967 -- Influence; HISTORY -- Middle East -- General; HISTORY -- Modern -- 20th Century; Arab-Israeli conflict; Influence (Literary, artistic, etc.); 1967-1973